Пріоритизація тестів як метод швидкого виявлення серйозних помилок - Malishevsky, Alexey G. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2010)
The use of information on the test costs and fault severities in the prioritization process in a regression testing is considered. Methods for estimation of test costs and fault severities are described. Fault severity is explored in relation to the program reliability. Three methods for incorporating the information into the prioritization process are investigated. The effects of the scale of test cost and fault severities on the efficiency of the methods for prioritization is established.